Weakly Bound States of Elementary Excitations in Graphene Superlattice in Quantizing Magnetic Field - Sergei V. Kryuchkov; Egor I. Kukhar’ (Advances in Condensed Matter Physics)
The spectrum of allowed energy of electron in graphene superlattice in the quantizing magnetic field is investigated. Such spectrum consists of number of so-called magnetic minibands. The width of these minibands depends on the superlattice barriers power and on the magnetic field intensity. The explicit form of electron spectrum is derived in the case of weak magnetic field. The possibility of electron-electron and electron-phonon bound states is shown. The binding energies of these states are calculated. The binding energy is shown to be the function of magnetic field intensity.